Solution of Improving the Packet Domain Gateway's Performance - Guohui Liu (Dianxin kexue)
With the increasing of the business, the internal logic of the packet domain gateway GGSN/SAE GW is becoming more and more complex. Meanwhile, the requirement to the performance of equipment is becoming higher and higher. In this way, the actual operational capability of the GGSN/SAE GW is far away from the safety working level. As a solution, it was focused on improving GGSN/SAE GW processing logic, adjusting the rank of NON-DPI top traffic to reduce the equipment load and enhance the operational capacity of the gateway effectively.